Pengaruh Media Visual Interaktif Dalam Pembelajaran Teknik Dasar Bola Voli Terhadap Minat Belajar Siswa - Sahabuddin; Anggi Setia Lengkana; Davi Sofyan (Indonesian Journal of Physical Activity, 2025)
This study aims to determine the effect of the use of interactive visual media in learning basic volleyball techniques on students' learning interest at SMP Negeri 13 Makassar. The method used is quasi-experimental with a pretest-posttest control group design. The sample consisted of 60 students divided into two groups, namely the experimental group that received learning using interactive visual media and the control group that used conventional methods. The instrument used was a learning interest questionnaire with a Likert scale of 1–5 that had been tested for validity and reliability. Data were analyzed using normality tests, homogeneity tests, and t-tests (paired sample t-test and independent sample t-test) with a significance level of 0.05. The results showed that the experimental group experienced an increase in learning interest scores from an average pretest of 58.4 to 78.6 in the posttest, while the control group only increased from 59.2 to 66.7. The t-test showed a significant difference between the experimental and control groups (t = 5.87; p < 0.05). These findings indicate that interactive visual media is effective in increasing students' interest in learning basic volleyball techniques. In conclusion, the application of interactive visual media as a learning medium can significantly increase students' interest in learning compared to conventional methods. Recommendations are given to PJOK teachers to integrate this media in the learning process to improve students' motivation and learning outcomes.